Estimation of land surface temperature based on GIS and remote sensing data in Dahuk city - Falih Naser, Nabaa; Fadhil Ibraheem, Israa; AlHadithi, Mufid; Janan Yosief, Fatin (Geodesy and Cartography, 2025)
Land Surface Temperature (LST) is a crucial variable across various domains, including studies on the global ramifications of climate change, urban land use and cover, and geo- and biophysical modelling. Satellite data from Landsat 8, specifically the NIR channel, was utilized to generate LST maps, NDVI, and LU/LC for Dahuk City. The correctness of LULC maps was verified by ground observation locations. The results indicate that the LST ranged from 4 to 14 degrees Celsius in 2013 and from 10 to 20 degrees Celsius in 2023. The highest temperatures, ranging from 14 to 20 degrees Celsius, occur in urban areas, whilst the lowest temperatures, recorded in 2013 and 2023, are in forests and aquatic environments, measuring 4 and 10 degrees Celsius, respectively and this occurred because of unplanned expansion of urban areas on behalf of green area as indicated by NDVI. Through this study planners and decision making could predict the future increase in LST if no action taken against these activities.